Penerapan Delapan Fungsi Keluarga dan Dampak Terhadap Kesejahteraan Keluarga Di Kabupaten Sorong - Benyamin Lado; Hugo Warami; Ihwan Tjolli (Cassowary, 2022)
This study aims to analyze the level of application of the eight family functions, the factors that influence and the effect of the level of application of the eight family functions on family welfare. The number of samples is 116 samples and the research methods are descriptive and quantitative. Data processing and analysis using multiple linear regression and simple linear regression. The results showed (1) the application of the eight family functions was in the medium category; (2) the results of multiple linear regression analysis, show that the variables of formal education, age, frequency of socialization together affect the level of implementation of the eight family functions; (3) the results of simple linear regression analysis show that the variable level of application of eight family functions has a significant effect on the level of family welfare.